Beliefs about Critical Thinking among English Teachers in Qasabet Al- Mafraq, Jordan - Ahmad, Zainab Salem (Journal of Educational and Psychological Sciences, 2020)
This study aimed to investigate the relationships between teachers' knowledge, beliefs and activities about critical thinking. . The study followed the descriptive approach. This research was based on a questionnaire designed to investigate English teachers' points of view about critical thinking for primary and secondary schools in Qasabet Al Mafraq which is a city in the north of Jordan The population of the study is 280 female and male teachers distributed through 160 primary and secondary school. The study sample was randomly selected and it represents 46% of all English teachers in Qasbet Al Mafraq. They are 40 male and 88 female teachers during the second semester 2018/2019.The results of the study indicate that most of the teachers know the higher and lower –order of critical thinking skills. Also, they are inclined to use the critical thinking strategy to achieve certain outcomes in the curriculum. According to the teachers' beliefs, they think critical thinking is an important and effective strategy for problem solving and decision making. On one hand, there is a positive correlation between teacher's knowledge, teachers' belief and critical thinking activitie such as role- playing, asking questions, problem- solving, conceptual maps, debate and game playing. But on the other hand, there are no statistically significant differences at (a= 0.05) due to the variables of gender, experience, number of students, and the stage they are teaching. The researcher recommends that more research should be done on the effect of critical thinking on the four skills reading, writing, speaking and listening.
Keywords: critical thinking; knowledge; beliefs